The development of Kiddo shield: fun children safety application - Othman, Azliza; Harun, Harryizman; Salleh, Nur Sakinah; Ahmad Faudzi, Siti Hajar (2019)
This article reports the development of Kiddo Shield Application. The Kiddo Shield Application was designed and developed to educate children to be aware of their safety in a different environment that is usually facing by them. Children are potentially at risk from injured and incident, especially when they are staying or playing alone. ADDIE model was adopted to design and develop the application. Interview with experts was employed regarding the interface design and content of the application. The review and comments from experts then analysed for further improvement. The majority of the experts agreed that the application developed is interesting for children, but improvements are necessary.